Söz-Metin Bağlamında Bakara Sûresi'nin 217: Ayeti Üzerine Bir Değerlendirme - Akay, Ali (Dinî araştırmalar, 2007)
In this article, I would like to evaluate al-Baqarah, 2/217 from the point of view of the context of text and discourse and to attract attention to importance of historical occasion of revelation and importance of distinctions between text and discourse in undrestanding of the Quran